For horse-crazy girls only : everything you want to know about horses - Wilsdon, Christina; Underhill, Alecia (New York : Feiwel and Friends, 2010)
Provides information about horses for horse-crazy girls, looking at the top ten horse breeds, popular horse names, favorite foods, coats and manes, tails, horses in the wild, horse clothes and gear, horse sports, horse movies, and other aspects of the animal.
Includes bibliographical references and index.
Publisher's Weekly
Publisher's Weekly, September 2010
3-6.
English.
Keywords: Horses -- Juvenile literature; Horses; Horses